DIGITAL COMPETENCE OF LANGUAGE LECTURERS AT PUTRA INDONESIA UNIVERSITY - Deri Fikri; Yusup Supyani (XXXXXXXX, 2024)
Digitalization is now widely required by any position, including in varsity level. The lecturers who hold an urgent position in teaching process must adapt easily to the latest technology update. Soon or later, technology development will push all workers if they want to survive in this era. How they use the technology development is the main concern of this study and how good the lecturers use digital thing in conducting the teaching-learning process.This study is aimed to draw the lecturers’ competency in using digital stuff in order to support their activity in teaching. The next target of this study is to give the Education and Culture Ministry a short possible overview about the lecturers’ competency in digital and is hoped to give comprehensive consideration on how to treat and guide the lecturers’ digital competency in the future.This is a qualitative research with the subjects of this research are the lecturers at Faculty of Humanities Putra Indonesia University. The technique of collecting data is conducted by triangulation methods, observation, interview and documentation. The result revealed that respondents have passed not only the standard set by the university but also criteria set by the theory.